Delinquency as a response to peer victimization: the implications of school and cyberbullying operationalizations - McCuddy, Timothy (Crime & delinquency, 2022)
As criminologists explore the link between bullying victimization and delinquency, they must grapple with measurement issues related to the operationalization of in-school bullying and cyberbullying. Accurately identifying victims has implications for school safety and implementation of policies to reduce the consequences of bullying. Using a longitudinal sample of over 2,000 students, we find youth who do not self-identify as victims of bullying but report peer victimization are likely to experience a number of criminogenic risk factors, and these “mismatched” victims are more likely than non-victims to engage in delinquency. While the observed consequences of victimization are similar across bullied and mismatched youth, we find that certain criminogenic risk factors are associated with failure to self-identify one’s victimization as bullying